CONNECTING BLOCKCHAINS WITH SOFTWARE SYSTEMS IN THE DIGITALIZATION OF THE HEALTHCARE SECTOR (World Bulletin of Public Health, 2026)
The article defines the concept of digital economy and blockchain, and provides information about its working system. Areas and areas of application of this technology are discussed. In particular, prospects for the application of "blockchain" technology and its effective use in the activities of economic entities and hospitals were considered